Synthesis of Green Carbon Dots from Nephelium Lappaceum L. Seeds - Kamali, Siti Raudhatul; Hamdiani, Saprini; Hermanto, Dhony; Saputri, Dinar Suksmayu; Chen, Chang-Nan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
In this study, rambutan (Nephelium Lappaceum L.) seeds were used to fabricate green carbon dots (gCDs) by employing a hydrothermal process. The synthesized CDs were evaluated using Fourier transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS) for the structural properties as well as UV-Vis and fluorescence spectrophotometry for the optical properties. UV-Vis examination revealed that the produced gCDs showed emission-dependent photoluminescence excitation, with two absorption peaks at 265 nm and 330 nm. The presence of functional groups and chemical composition such as C=C, C=O, -COOH, and -OH on the surface of gCDs was confirmed by the results of FTIR and XPS spectra. Consequently, gCDs present several opportunities for exploration in a range of applications.